2019
DOI: 10.1534/g3.118.200852
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Transcriptome Analysis Reveals Candidate Genes for Terpenoid and Phenylpropanoid Metabolism in the Medicinal PlantFerula assafoetida

Abstract: Ferula assafoetida is a medicinal plant of the Apiaceae family that has traditionally been used for its therapeutic value. Particularly, terpenoid and phenylpropanoid metabolites, major components of the root-derived oleo-gum-resin, exhibit anti-inflammatory and cytotoxic activities, thus offering a resource for potential therapeutic lead compounds. However, genes and enzymes for terpenoid and coumarin-type phenylpropanoid metabolism have thus far remained uncharacterized in F. assafoeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Detailed results are displayed in Table S2, Supplementary Materials . The level of transcriptome completeness depends on the amount of tissues and developmental stages within the samples [ 14 ]. Therefore, we would expect a limited set of detected BUSCOs in our tissue-specific analysis of meristematic embryo cells.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed results are displayed in Table S2, Supplementary Materials . The level of transcriptome completeness depends on the amount of tissues and developmental stages within the samples [ 14 ]. Therefore, we would expect a limited set of detected BUSCOs in our tissue-specific analysis of meristematic embryo cells.…”
Section: Resultsmentioning
confidence: 99%
“…By analysing the DEGs in the root, researchers revealed the pathway of tanshinone biosynthesis in S. miltiorrhiza [29]. Tissue-speci c genes, play important roles in plant defence, stress response, plant development and material metabolism [41,42,[80][81][82][83]. In Ferula asafetida, genes involved in terpenoid and phenylpropanoid metabolism tended to be expressed in the owers [83].…”
Section: Discussionmentioning
confidence: 99%
“…Tissue-speci c genes, play important roles in plant defence, stress response, plant development and material metabolism [41,42,[80][81][82][83]. In Ferula asafetida, genes involved in terpenoid and phenylpropanoid metabolism tended to be expressed in the owers [83]. In the study of tomato (Solanum pennellii), researchers concluded that tissue-speci c genes play important regulatory roles during fruit development [41].…”
Section: Discussionmentioning
confidence: 99%
“…Further, differential expression analysis between the corm, leaf and flower provides a reduced set of uncharacterised genes that narrows down the list of genes possibly imparting medicinal properties to the corm. Cross-tissue transcriptomic analyses have been performed in the past to identify candidate genes involved in the biosynthesis of secondary metabolites in medicinal plants like Ferula asafoetida, Dysphania schraderiana and Salvia miltiorrhiza [21][22][23]. In this study, aside from transcriptomic analyses, proteomic profiling was performed on the flower, leaf and corm tissues from Hypoxis hemerocallidea.…”
Section: Introductionmentioning
confidence: 99%